Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Dalam Menyelesaikan Soal- Soal Geometri Bangun Ruang - ilham, ilham; Jabnabillah, Faradiba; Astiati, Siska Dwi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Students' mathematical problem solving ability is one thing that must be considered. This is because when students are given problem solving problems in the form of routine students are able to solve these problems, but if a non-routine problem arises, students will have difficulty. During teaching and learning activities students are able to solve problems when presented with questions of the same type. However, if given a variety of questions, some students have difficulty working on them. This study aims to explore and describe students' mathematical problem solving abilities in solving spatial problems. This study uses a descriptive qualitative approach. The data analysis technique in this study used descriptive analysis techniques. The results of the analysis show that high-ability subjects can understand the problem by writing steps, solving problems, re-examining the results of work very precisely and correctly. Students with moderate abilities can only solve problems without writing what is known and asked. Meanwhile, low-ability students cannot fulfill all aspects of mathematical problem solving.